1998
DOI: 10.1099/00221287-144-1-219
|View full text |Cite
|
Sign up to set email alerts
|

Rhodobacter capsulatus genes encoding form I ribulose-1,5-bisphosphate carboxylase/oxygenase (cbbLS) and neighbouring genes were acquired by a horizontal gene transfer

Abstract: Analysis of the nucleotide sequence of the form I ribulose-1.5-bisphosphate carboxylase/oxygenase (RubisCO) genes (cbbL and ebbs) of the non-sulfur purple bacterium Rhodobacter capsulatus indicated that the deduced amino acid sequence of the large subunit was not closely homologous to the large subunit from related organisms. Indeed, phylogenetic analysis suggested that the large subunit protein (Cbbl) more closely resembled the enzyme from alpy purple bacteria and cyanobacteria and is within a 'green-like' ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 36 publications
3
53
0
5
Order By: Relevance
“…have two forms of RubisCO (form I and form II). Comparisons of the form I complex between Rhodobacter capsulatus and R. sphaeroides provided evidence that they were more divergent than previously anticipated (Paoli et al, 1998;Horken & Tabita, 1999). Phylogenetic studies confirmed that the form I complex of R. capsulatus was more closely related to the 'green-type' RubisCO group, associated with a/b/c chemoautotrophic proteobacteria, and green algae, than the 'red-type' found in a/b bacteria and the plastids of red algae.…”
Section: S E Maddocks and P C F Oyston 3612mentioning
confidence: 77%
See 1 more Smart Citation
“…have two forms of RubisCO (form I and form II). Comparisons of the form I complex between Rhodobacter capsulatus and R. sphaeroides provided evidence that they were more divergent than previously anticipated (Paoli et al, 1998;Horken & Tabita, 1999). Phylogenetic studies confirmed that the form I complex of R. capsulatus was more closely related to the 'green-type' RubisCO group, associated with a/b/c chemoautotrophic proteobacteria, and green algae, than the 'red-type' found in a/b bacteria and the plastids of red algae.…”
Section: S E Maddocks and P C F Oyston 3612mentioning
confidence: 77%
“…Form II was also shown to have its own endogenous CbbR divergently transcribed from the cbbM gene. The regulators are currently referred to as CbbR I and CbbR II (Paoli et al, 1998). A classical LTTR box (TTA-N 7/8 -TAA) is found upstream of both cbbLSQ and cbbM.…”
Section: S E Maddocks and P C F Oyston 3612mentioning
confidence: 99%
“…In contrast, the phylograms of the RuBisCO large-subunit genes, cbbL and cbbM, are not similar to those based on 16S rDNA. The inconsistency between the RuBisCO gene distribution and the 16S rDNAbased affiliation among several groups of autotrophic proteobacteria, cyanobacteria, and green eukarya was previously ascribed to the multiple horizontal gene transfers of RuBisCO genes in different phylogenetic lineages (7,52).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests (unless the tree is wrong and they really form a single clade) that the cenancestor had rubisco and that it was lost by green bacteria and spirochaetes or that rubisco evolved in one clade and moved to the other by lateral gene transfer. As there is evidence for a relatively recent lateral gene transfer of rubisco between these two clades (Paoli et al 1998), it is possible that it occurred also in their early evolution; however, we should bear in mind that lateral gene transfer by replacement of a functionally equivalent activity, as in this case, may be intrinsically easier than acquiring a new function. Loss of rubisco has also probably occurred, as it is absent from the posibacterial heliobacteria, but was almost certainly present in the common ancestor of cyanobacteria and posibacteria.…”
Section: The Greening Of Life: Photosynthetic Protocellsmentioning
confidence: 99%